2015
DOI: 10.1002/adem.201400585
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of (TiC + Ti3SiC2 + Ti5Si3)/Ti6Al4V Composites with Tailored Two‐scale Architecture

Abstract: In situ TiC particle, Ti 3 SiC 2 bar and ultrafine Ti 5 Si 3 needle reinforced Ti6Al4V (TiCþTi 3 SiC 2 þTi 5 Si 3 )/Ti6Al4V) composites with a tailored distribution were sucessfully designed and fabricated. The first-scale tailored architecture of reinforcement is the in situ synthesized Ti 3 SiC 2 bars and nearequiaxed TiC particles on the network boundary around Ti6Al4V particles. The secondary-scale architecture is the ultrafine Ti 5 Si 3 needles precipitated in intergranular b phase of center Ti6Al4V matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…[32,33] . 进一步观察发现, 网状结构内部基体中的α/β 相界处或β相附近分布着尺寸细小的第二相析出增强 相, 这对β相起到了细化作用, 使得制备的钛基复合材 料中的β相发生了明显细化 [24,34] . .…”
Section: 脱溶析出 获得了两级网状结构(Tic+ti 3 Sic 2 +Ti 5 Si 3 )/Tc4unclassified
“…[32,33] . 进一步观察发现, 网状结构内部基体中的α/β 相界处或β相附近分布着尺寸细小的第二相析出增强 相, 这对β相起到了细化作用, 使得制备的钛基复合材 料中的β相发生了明显细化 [24,34] . .…”
Section: 脱溶析出 获得了两级网状结构(Tic+ti 3 Sic 2 +Ti 5 Si 3 )/Tc4unclassified
“…[21,36,42,43,85,[145][146][147] Figure 14 shows the extraordinary tensile properties of Ti-6Al-4V reinforced with TiB nanowires compared with those reinforced with micro-sized ceramics and mill-annealed and STA Ti-6Al-4V and Ti-10V-2Fe-3V. [1,24,26,36,38,41,[148][149][150][151][152][153] As suggested by Equation (3), increasing the aspect ratio of reinforcements is another efficient strategy to enhance the mechanical properties of TiMMCs. [154] Koo et al [21] showed that the yield strength of Ti-6Al-4V/1 vol% TiB increased from 900 to 1075 MPa when the aspect ratio of TiB whiskers was increased Figure 13.…”
Section: Reinforcement Size and Aspect Ratiomentioning
confidence: 99%
“…In addition, silicide ceramics demonstrated better deformation characteristics than other compounds like carbides and borides [20]. Specifically, the silicide of Ti 5 Si 3 exhibits a high melting point, low density, pronounced creep resistance, high fracture toughness over 1000 • C, good oxidation resistant behavior, and a thermal expansion coefficient closely matching that of titanium [21][22][23]. In this context, this work presents the investigation of a titanium alloy incorporating titanium silicide precipitates.…”
Section: Introductionmentioning
confidence: 99%